Effects of Two Weeks Finasteride Therapy on Per-Operative Decrease in Haemoglobin Patients after Transurethral Resection of Prostate (TURP) - Qazi Naeem, Zeeshan Arshad, Haseeb Amjad, Muhammad Abdul Rauf, Safdar Saeed, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To compare the per-operative mean decrease in haemoglobin level in patients undergoing transurethral resection of prostate taking finasteride for two weeks before transurethral resection of prostate versus without pre-treatment of finasteride. Study Design: Randomized control trial Place and Duration of Study: Department of Urology, Indus Hospital, Karachi from 23rd May 2017 to 22nd November 2017. Methodology: Sixty patients were included and divided into two groups. In Group A, patients were finasteride (5 mg/day) for two weeks before surgery and Group B (control group) no drug will be given before surgery. All patients underwent transurethral resection of prostate and then had intra-operative bleeding noted. Results: Only 4 (8.7%) of the patients had the history of supplement use. No significant difference was observed in age, baseline creatinine, protate size, duration of BPH, before surgery hemoglobin and after surgery hemoglobin between both the groups. There was slight decrease in hemoglobin in placebo group adjusting for age, baseline creatinine, duration of BPH and prostate size. However, the results did not reach statistical significance. Conclusion: Finesteride given 2 weeks prior to surgery does not significantly decrease intra-op bleeding. Keywords: Effect, transurethral resection of prostate (TURP), Finasteride